The Influence of Carbon Emissions and Corporate Social Responsibility (CSR) on the Financial Performance of Transportation Companies Listed on the Indonesia Stock Exchange - Rufiatun, Yayuk (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the effect of carbon dioxide (CO₂) emissions and Corporate Social Responsibility (CSR) on the financial performance of transportation companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. Financial performance is measured using Return on Asset (ROA) as the dependent variable, while carbon emissions and CSR serve as the independent variables. The study employs a quantitative approach using panel data regression with a common effect model. A total of 15 transportation companies were selected through purposive sampling, resulting in 90 balanced panel data observations. The results show that carbon emissions do not have a significant effect on ROA, indicating that environmental issues are not yet a primary concern in the business strategies of transportation companies. Conversely, CSR has a negative and significant effect on ROA, which may be due to the high costs of CSR implementation that have not yet generated short-term financial returns for the companies. The R-squared value of 5.68% indicates that the model explains only a small portion of the variation in financial performance. These findings highlight the importance of fully integrating sustainability strategies to create long-term value for companies.